Cover Story : A new look at Bookbinding. - Sykes, Diana A. (s.l. : s.n., 1994)
Hicks, Chris ; James, Angela ; Jones, Trevor ; Lindsay, Jen ; Middleton, Bernard ; Powell, Roger ; Robinson, Ivor ; Saumarez Smith, Romilly ; Sellars, David ; Shannon, Faith ; Smith, Philip ; Smith, Sally Lou
Exhibition of works by Designer Bookbinders, The Crawford Arts Centre, 25 march - 24 april 1994
boek